Endoscopic Cyanoacrylate Injection Versus Balloon‐Occluded Retrograde Transvenous Obliteration for Prevention of Gastric Variceal Bleeding: A Randomized Controlled Trial. Issue 4 (14th September 2021) - Luo, Xuefeng; Xiang, Tong; Wu, Junchao; Wang, Xiaoze; Zhu, Yongjun; Xi, Xiaotan; Yan, Yuling; Yang, Jinlin; García‐Pagán, Juan Carlos; Yang, Li
Abstract : Background and Aims: The optimal treatment for gastric varices (GVs) is a topic that remains open for study. This study compared the efficacy and safety of endoscopic cyanoacrylate injection and balloon‐occluded retrograde transvenous obliteration (BRTO) to prevent rebleeding in patients with cirrhosis and GVs after primary hemostasis. Approach and Results: Patients with cirrhosis and history of bleeding from gastroesophageal varices type 2 or isolated gastric varices type 1 were randomized to cyanoacrylate injection (n = 32) or BRTO treatment (n = 32). Primary outcomes were gastric variceal rebleeding or all‐cause rebleeding. Patient characteristics were well balanced between two groups. Mean follow‐up time was 27.1 ± 12.0 months in a cyanoacrylate injection group and 27.6 ± 14.3 months in a BRTO group. Probability of gastric variceal rebleeding was higher in the cyanoacrylate injection group than in the BRTO group ( P  = 0.024). Probability of remaining free of all‐cause rebleeding at 1 and 2 years for cyanoacrylate injection versus BRTO was 77% versus 96.3% and 65.2% versus 92.6% ( P  = 0.004). Survival rates, frequency of complications, and worsening of esophageal varices were similar in both groups. BRTO resulted in fewer hospitalizations, inpatient stays, and lower medical costs. Conclusions: BRTO is more effective than cyanoacrylate injection in preventing rebleeding from GVs, with similar frequencies of complications and mortalities.